Penguins - Markert, Jenny ([Mankato, Minn.] : Child's World ; Chicago, Ill. : Distributed to schools and libraries in the U.S. by Encyclopaedia Educational Corp., 1991)
Describes the physical characteristics, behavior, and habitat of penguins.
Keywords: Penguins; Penguins